Comparative study of efficacy and safety of parenteral iron sucrose versus ferric carboxymaltose in treatment of postpartum iron deficiency anaemia - Dakhle, Ganesh N.; Kalikar, Mrunalini V.; Fuke, Rujuta P.; Parmarthi, Anisha S.; Chokhandre, Mrunalini K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Postpartum anaemia often leads to multiple clinical complications in mother as well as infant and iron supplementation with parenteral iron is the preferred treatment modality. The present study was planned to compare the efficacy and tolerability of IV iron sucrose and IV ferric carboxymaltose in treatment of postpartum iron deficiency anaemia. Methods: This randomized, parallel, open label, prospective 4-weeks study was conducted from June 2019 to December 2020 in women with postpartum anaemia admitted to obstetrics and gynaecology inpatient department of a tertiary care hospital. Women with postpartum iron deficiency anaemia (N=60) were randomly divided into two groups; receiving Injection iron sucrose (N=30, maximum dose 500 mg) or Injection ferric carboxymaltose (N=30, maximum dose 500 mg). Change in haemoglobin and serum ferritin levels from baseline to the end of 2 and 4 weeks of treatment were evaluated. Results: The results showed early, sustained and significant increase in the haemoglobin levels in both the groups. However, the difference was not significant between groups (p=0.2). Evaluation of replenishment of iron stores (serum ferritin) showed improvement in both the groups, however in FCM group the rise was found to be significant (p<0.05). Conclusions: FCM in a lower dose of 500mg was found to be safe and effective in significantly improving haemoglobin concentration as well as in replenishing iron stores in patients with postpartum anaemia.